The serial changes of Neutrophile-Lymphocyte Ratio and correlation to weight loss after Laparoscopic Sleeve Gastrectomy - Chi, Po-Jui; Wu, Kun-Ta; Chen, Po-Jen; Chen, Chung-Yen; Su, Yu-Chieh; Yang, Chung-Yi; Chen, Jian-Han (Frontiers in Surgery, 2022)
Purpose: This study aims to identify the pre- and postoperative changes in the neutrophil-lymphocyte ratio (NLR) and its correlations to clinical characteristics in obese patients who underwent laparoscopic sleeve gastrectomy (LSG). Method: Retrospectively, we included patients who has undergone LSG in our institution between January 2019 and April 2021. A total of 100 patients whose body mass index over 32.5 and received primary laparoscopic sleeve gastrectomy without infectious condition were included. Results: There was a significant decline in NLR (T0 vs. POM3 2.21 vs. 1.78, p=0.005), neutrophil (T0 vs. POM3 5369 vs. 4050, p<0.001) and lymphocyte count (T0 vs. POM3 2440: 2100, p<0.001, respectively) at postoperative 3 months (POM3) compared to preoperative (T0) levels, but similar between POM3 and POM6. The declined counts (Neutrophile vs. Lymphocyte 1445.5/uL vs. 323.5/uL, p<0.001) and percentage (Neutrophile vs. Lymphocyte 25.11% vs. 13.07%, p<0.001) of neutrophile are higher than lymphocyte from T0 to POM3, but similar in POM3 and POM6. Preoperative NLR has a significant correlation with the preoperative body weight, preoperative insulin level, and excessive body weight loss (EBWL) at POM3. Preoperative NLR < 2.36 had a sensitivity of 67.6% and a specificity of 62.5% in predicting successful weight loss (EBWL>37.7%) at POM3 (AUC = 0.635, p=0.032). Conclusion: There was a significant decline in NLR, neutrophil, and lymphocyte count from T0 to POM3, but similar between POM3 and POM6. The declined counts and percentage of neutrophile are higher than lymphocyte. Preoperative NLR shows the potential to be used as a prognostic biomarker for predicting successful weight loss at POM3 after LSG. Further studies could be designed to evaluate the value of prediction in successful outcome after LSG and figure out the relationship between the changes of neutrophil function and oncogenesis.